Exploring Students’ Perception and Belief of Extensive Reading Program in Improving Reading Ability and Language Competences - Anggraini, Winda Ari (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
The aim of this research was to investigate students’ perception toward a small-scale project of extensive reading (ER) program. ER is believed can improve many aspects of language skills, including vocabulary, reading speed, listening, speaking, and writing (Day and Bamford, 1998; Renandya, 2007). Therefore, research participants were also asked about their view on reading ability and other linguistic competences improvement. This research utilized case study specifically focused on three students who showed outstanding progress through the project, using semi-structured interview for data collection. The paper concludes with positive results for both students’ perception and their reading ability and language competence.